2014
DOI: 10.1016/j.jcma.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preprocedural anxiety levels on pain perception in patients undergoing office hysteroscopy

Abstract: The pain that study participants felt during and soon after OH was negatively affected by preprocedural anxiety levels. Some factors, such as reducing the waiting time before the procedure, might be useful in reducing anxiety levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
34
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 15 publications
7
34
2
8
Order By: Relevance
“…26 Kokanali also found a positive correlation between waiting time and anxiety with increased pain scores. 24 Our data do not support a correlation between STAI form Y1 (trait anxiety) and an increased pain score. As to STAY form Y2 (state anxiety), data showed a very modest correlation between state anxiety and pain.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…26 Kokanali also found a positive correlation between waiting time and anxiety with increased pain scores. 24 Our data do not support a correlation between STAI form Y1 (trait anxiety) and an increased pain score. As to STAY form Y2 (state anxiety), data showed a very modest correlation between state anxiety and pain.…”
Section: Discussioncontrasting
confidence: 80%
“…23 OH patients may have higher VAS scores with longer waiting time and women with higher STAI scores may experience more pain or indeed there may not be any correlation between STAI and VAS scores. [24][25][26] Distractions such as music may be associated with lower pain and anxiety. 27 As to patient satisfaction questionnaires, how well do they correlate with pain score?…”
Section: Introductionmentioning
confidence: 99%
“…OH patients may have higher VAS scores with longer waiting time 23,24 and distractions such as music may be associated with lower pain and anxiety. 25 But the question remains, are there clinical predictors associated with pain perception at hysteroscopy?…”
Section: Introductionmentioning
confidence: 99%
“…3 In the Chinese Journal of Medical Association, the same group of authors previously published a similar study and obtained similar results. 4 The end results of their study showed that there were significantly positive correlations between preprocedural traitestat levels and procedurerelated pain [as assessed by the visual analogue scale (VAS)] during office hysteroscopy. 4 In addition, the authors also found that in-hospital waiting time was the most important factor contributing to high VAS during office hysteroscopy, 4 suggesting that further consideration should be devoted to improving patient care.…”
mentioning
confidence: 99%
“…4 The end results of their study showed that there were significantly positive correlations between preprocedural traitestat levels and procedurerelated pain [as assessed by the visual analogue scale (VAS)] during office hysteroscopy. 4 In addition, the authors also found that in-hospital waiting time was the most important factor contributing to high VAS during office hysteroscopy, 4 suggesting that further consideration should be devoted to improving patient care. Effectively finding avenues to decrease patient anxiety might also be a key factor in improving patient compliance and satisfaction when patients are being prepped to undergo any intensive procedure and therapy.…”
mentioning
confidence: 99%